Healthy tourism initiatives at destinations: opportunities and challenges - I Made Ady Wirawan (Public Health and Preventive Medicine Archive, 2018)
Last but not least is the interaction between the various professions in the health sector especially doctors, nurses, and public health experts. This inter-professional collaboration coupled with cross-sectoral collaboration with the tourism sectors, including the government and the tourism industry, will play a major role in the realization of tourism health efforts in accordance with the concepts described in this article. If this can work well, a vision for healthy tourism can be a reality.